2009
DOI: 10.1097/ncc.0b013e3181982d18
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Quality of Life in Men With Prostate Cancer

Abstract: Each of the successful treatment options for men with prostate cancer is accompanied by its unique side effect profile. However, treatment with androgen deprivation therapy (ADT) and the resulting castrate level of testosterone lead to profound changes in one's physical appearance. The goal of this descriptive study was to describe the relationship between changes in body image and quality of life (QOL) among prostate cancer survivors based upon whether or not treatment was with ADT. A convenience sample of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 33 publications
1
41
0
1
Order By: Relevance
“…Schover et al 22 observed that having a sexual partner was 1 predictor of successful sexual rehabilitation after cancer treatment. An association between changes in body image and quality of life is generally reported after cancer treatments 23 and, in the current study, may particularly have affected survivors with smaller testicular size.…”
Section: Discussionmentioning
confidence: 91%
“…Schover et al 22 observed that having a sexual partner was 1 predictor of successful sexual rehabilitation after cancer treatment. An association between changes in body image and quality of life is generally reported after cancer treatments 23 and, in the current study, may particularly have affected survivors with smaller testicular size.…”
Section: Discussionmentioning
confidence: 91%
“…Selected publications represented five continents and 10 countries including the United States (Stein & Zera , Fobair et al . , Harrington & Badger , Fingeret et al . , , , , Rhoten et al .…”
Section: Resultsmentioning
confidence: 99%
“…Gynaecomastia is particularly problematic. 24,25 Some individuals are less bothered and able to adapt to, or ignore, or in some cases even autoeroticize these feminisation changes. 26 However, most men tend to deal with gynaecomastia by hiding it and this can lead to social isolation.…”
Section: Body Feminisationmentioning
confidence: 99%